WASH maintains NKp46+ ILC3 cells by promoting AHR expression - Pengyan Xia (Nature Portfolio, 2017)
Innate lymphoid cells (ILC) are thought to direct immune responses, but little is known about the development and maintenance of ILC subsets. Here the authors show that WASH maintains the pool of NKp46+ ILC3s by recruiting Arid1a to the aryl hydrocarbon receptor promoter and inducing its expression.